Growth of TiO2 thin films by Atomic Layer Deposition (ALD) - Hussin, Rosniza; Kwang, Leong Choy; Xiang, Hui Hou (Trans Tech Publications, 2016)
Ceramic oxide thin films are an important material, with applications in many areas of science and technology. Titanium oxide (TiO2) is also a well-known and important material for applications such as gas sensors [1], photocatalysis materials [3], and electrochemicals [1], due to its self-cleaning [2], good corrosion resistance and biocompatibility. Atomic Layer Deposition (ALD) is a nanotechnology tool that is used for the deposition of nanostructured thin films. The unique advantage of ALD is the self-limiting film growth mechanism, which offers attractive properties, simple and accurate film thickness control, sharp interfaces, uniformity over large areas, excellent conformality, good reproducibility, a multilayer processing capability, and high quality films at low temperatures [3, 4]. TiO2 thin films were grown using TTIP (Titanium isopropoxide) ALD on silicon wafers, glass slides, and stainless steel plates in order to study the effect of substrates on the growth of TiO2. In order to achieve the desired advantages of using TTIP, a series of experiments were performed to study the growth mechanism of TiO2 thin films using TTIP and H2O by ALD.